Service user experiences of risk assessment and management in a low secure service. Issue 2 (4th March 2021) - Gray, Hannah; Clarke, Caroline; Sambrook, Suzanne; Lee, Laura
ABSTRACT: Risk assessment and management are core features within forensic services. With the implementation of recovery principles, there has been more investment in adopting collaborative approaches in this process. This paper explores five service user perspectives of collaborative risk assessment and management within a low secure service. Semi-structured interviews were analysed using Interpretative Phenomenological Analysis which produced two superordinate themes: 'Snakes and Ladders' and 'Knowledge is Power'. Although there have been positive experiences of collaborative risk, more work needs to be done to develop collaborative working throughout the risk process. The findings are consistent with the forensic literature. Clinical implications and directions for future research are discussed.